AIAA Guidance, Navigation, and Control Conference and Exhibit 2001
DOI: 10.2514/6.2001-4094
|View full text |Cite
|
Sign up to set email alerts
|

An efficient algorithm for vibration suppression to meet pointing requirements of optical payloads

Abstract: For several future imaging spacecraft, vibration isolation and suppression of its optical payloads have become a challenging problem. These spacecraft have increased performance requirements for the payload, resulting in increased fine steering and vibration isolation requirements. The vibration sources on the spacecraft, however, are increased due to the new large flexible structures and addition of rotating devices. One promising way to address both issues is through the Stewart platform. By using a hexapod … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…It makes use of a set of three Eddy current sensors to determine the tip and tilt angle for pointing, whereas the other motion variables, including the rotation about the vertical axis of symmetry, are assumed to be zero. Pointing experiments using this measurement system has been done with reasonable results 2,3,4 . However, it is observed that the sensors can easily be influenced by environment magnetic noise and the Plexiglas posts of the setup are not rigid enough to keep away from the influence of vibrating disturbances.…”
Section: Introductionmentioning
confidence: 88%
“…It makes use of a set of three Eddy current sensors to determine the tip and tilt angle for pointing, whereas the other motion variables, including the rotation about the vertical axis of symmetry, are assumed to be zero. Pointing experiments using this measurement system has been done with reasonable results 2,3,4 . However, it is observed that the sensors can easily be influenced by environment magnetic noise and the Plexiglas posts of the setup are not rigid enough to keep away from the influence of vibrating disturbances.…”
Section: Introductionmentioning
confidence: 88%
“…The ADC method 24 was specially developed for sine vibration control of SISO system, as shown in Figure 4. Since the expected output signal d ( t ) can be constructed with reference sine and cosine signal…”
Section: Basic Theory and Sine Vibration Generationmentioning
confidence: 99%
“…where w 1 , w 2 are tunable parameters, and the iteration equation based on LMS algorithm for w 1 , w 2 is 24…”
Section: Basic Theory and Sine Vibration Generationmentioning
confidence: 99%
“…The precision of the optical equipment on spacecraft is continuing to increase, which has led to improvements in the performance of vibration isolation devices. Additionally, due to the introduction of a new flexible structure and rotating device, vibration sources have become increasingly prominent [1]. Although a passive isolation system offers a simple and reliable means of protecting precision equipment from a vibration environment, active vibration isolation has significantly improved the performance of such systems.…”
Section: Introductionmentioning
confidence: 99%